Right of Religious Freedom and Belief (Case Studi Al-Zaytun Islamic Boarding School in Indramayu) - Martalia, Martalia; Sabna, Anjali (Al-Adyan: Journal of Religious Studies, 2024)
Freedom of religion and belief is a reality of life, where everyone is free to choose their religion or belief. However, this remains an unresolved issue in Indonesia. This article aims to examine the application and boundaries of the internal and external forums regarding freedom of religion and belief in Indonesia, highlighting the case of Al-Zaytun Islamic boarding school. The research employs a literature review method, followed by descriptive analysis of related studies. The findings indicate potential discrepancies in the implementation with principles outlined in internationally ratified covenants by Indonesia. Referring to the provisions of the International Covenant on Civil and Political Rights (ICCPR), there exists freedom within internal and external forums. The internal forum pertains to the realm within an individual's mind or consciousness, acknowledging personal beliefs and religion as internal matters. Meanwhile, the external forum represents a dimension where freedom is manifested in actions and practiced collectively with others or in public spaces. Ratification by the state aims to uphold human rights and ensure fair legal protection for every individual.Kebebasan beragama dan berkeyakinan merupakan realitas kehidupan, dan setiap orang bebas memilih agama atau keyakinannya. Namun, ini masih menjadi persoalan yang belum terselesaikan di Indonesia. Tulisan ini bertujuan untuk melihat penerapan serta batasan forum internum dan eksternum tentang kebebasan beragama dan berkeyakinan di Indonesia dengan menyoroti kasus Pondok pesantren Al-Zaytun. Penelitian ini dilakukan menggunakan metode literature review yang kemudian dianalisis secara deskriptif melalui data kajian yang berkaitan. Hasil studi ini menunjukkan dari kasus yang terjadi pada pondok pesantren Al-Zaytun, adanya potensi ketidaksesuaian penerapan dengan prinsip-prinsip yang diatur dalam kovenan internasional yang telah di ratifikasi oleh Negara Indonesia. Merujuk pada ketetapan Kovenan Internasional Hak Sipil dan Politik (KIHSP) terdapat kebebasan dalam forum internal dan eksternal. Forum internal berada pada ruang yang ada dalam pikiran atau kesadaran individu. Forum ini mengakui keyakinan, dan agama yang merupakan urusan internal sifat pribadi seseorang. Sementara Forum eksternal merupakan suatu dimensi di mana kebebasan telah diwujudkan dalam tindakan dan dilaksanakan bersama-sama dengan orang lain atau di ruang publik. Pengesahan dari negara ini bertujuan untuk menjunjung tinggi hak asasi manusia serta perlindungan hukum yang adil bagi setiap individu.